2014
DOI: 10.1007/s10865-014-9592-3
|View full text |Cite
|
Sign up to set email alerts
|

The association between mindfulness and emotional distress in adults with diabetes: Could mindfulness serve as a buffer? Results from Diabetes MILES: The Netherlands

Abstract: People with diabetes have a higher risk of emotional distress (anxiety, depression) than non-diabetic or healthy controls. Therefore, identification of factors that can decrease emotional distress is relevant. The aim of the present study was to examine (1) the association between facets of mindfulness and emotional distress; and (2) whether mindfulness might moderate the association between potential adverse conditions (stressful life events and comorbidity) and emotional distress. Analyses were conducted usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 40 publications
2
23
0
Order By: Relevance
“…First, although our results suggest that subjective sleep impairment is common in both adults with type 1 and type 2 diabetes, our prevalence estimates may be biased, as our self-selected sample is not fully representative of all adults with type 1 and type 2 diabetes in The Netherlands. In our study, adults with type 2 diabetes not using insulin, those from ethnic minority groups, and people with co-morbid vascular conditions and emotional distress were under-represented [25,37]. However, a previous study among adults with type 1 diabetes found a similar prevalence of self-reported poor sleep quality (35%) [9].…”
Section: Strengths and Limitationsmentioning
confidence: 48%
“…First, although our results suggest that subjective sleep impairment is common in both adults with type 1 and type 2 diabetes, our prevalence estimates may be biased, as our self-selected sample is not fully representative of all adults with type 1 and type 2 diabetes in The Netherlands. In our study, adults with type 2 diabetes not using insulin, those from ethnic minority groups, and people with co-morbid vascular conditions and emotional distress were under-represented [25,37]. However, a previous study among adults with type 1 diabetes found a similar prevalence of self-reported poor sleep quality (35%) [9].…”
Section: Strengths and Limitationsmentioning
confidence: 48%
“…However, no studies have been conducted on the association between dispositional mindfulness and eating behaviour in people with type 1 or type 2 diabetes. In addition, in most studies, symptoms of psychological distress have not been controlled for, while these symptoms may confound associations as they are related to both eating behaviour (Blaine, 2008) and mindfulness (Baer et al, 2006;Brown & Ryan, 2003; in people with diabetes: Van Son, Nyklíček, & Nefs, et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For example, among patients with diabetes, stressful life events were not associated with feelings of depression in those who scored high on the three mindfulness facets (Van Son et al, 2015). Among patients with rheumatoid arthritis, disability was related to less psychological distress at one year follow-up when mindfulness was high .…”
Section: Discussionmentioning
confidence: 94%
“…Recent studies investigated whether mindfulness could serve as a 'buffer' which protects against negative effects of stressful events up to one year follow-up (Bränström et al, 2011;Nyklíček, Hoogwegt, & Westgeest, 2015;Van Son et al, 2015). For example, among patients with diabetes, stressful life events were not associated with feelings of depression in those who scored high on the three mindfulness facets (Van Son et al, 2015).…”
Section: Discussionmentioning
confidence: 99%